2017
DOI: 10.3311/ppci.9652
|View full text |Cite
|
Sign up to set email alerts
|

Predicting Displacement Data of Three-Dimensional Reinforced Concrete Frames with Different Strengthening Applications Using ANN

Abstract: In this study, the artificial neural network (ANN)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2018
2018
2019
2019

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 19 publications
0
3
0
Order By: Relevance
“…The tests of specimens were tested under lateral loading and constant vertical loading (Bahadır and Balık, 2017). The applied lateral loading was reversed cyclic loading that simulates the earthquake executions .…”
Section: Test Setupmentioning
confidence: 99%
See 1 more Smart Citation
“…The tests of specimens were tested under lateral loading and constant vertical loading (Bahadır and Balık, 2017). The applied lateral loading was reversed cyclic loading that simulates the earthquake executions .…”
Section: Test Setupmentioning
confidence: 99%
“…Besides, researches had shown that, a big majority of the existing reinforced concrete (RC) buildings in Van-Ercis earthquake are seismically deficient (EERC, 2011). These deficiencies were low-strength materials, no column stirrups at the beam-column joints, strong beam-weak column formation, no confinement zones at the end of the columns beams, and wide spacing of beam and column stirrups (EERC, 2011;Bahadır and Balık, 2017). Because of these deficiencies, these buildings had an insufficient lateral load carrying capacity, lateral stiffness, energy dissipation capacity and ductility.…”
Section: Introductionmentioning
confidence: 99%
“…5 Similar studies were conducted by other researchers. [6][7][8][9] In this study, various national building codes were compared regarding the structural-system irregularities to reveal the differences.…”
Section: Introductionmentioning
confidence: 99%